Analysis And Implementation Of Turnaround Strategies And Their Impact On Company Performance: A Case Study Of An Outsourcing Company - Carolina Radjawane; Eka Pria Anas (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze and describe turnaround strategies and how their implementation affects company performance. This study employs a qualitative case study approach on PT DPS, an outsourcing company with head office in Tangerang, analyzing qualitative data gathered through in-depth semi-structured interviews with the company's senior management, as well as analyzing quantitative data obtained through examination of the company’s reports and documentation. The study employs financial ratios to assess the company's financial performance and uses the Altman Z-score to evaluate the company's bankruptcy risk. The implementation of turnaround strategies has led to improvements in the company's performance, including profitability, liquidity, asset management, and the Altman Z-score. However, the company is expected to remain in a net loss position and not yet entirely free from the risk of bankruptcy by the end of 2024. Research on outsourcing companies is scarce, particularly studies focusing on outsourcing companies facing financial distress and implementing turnaround strategies. Previous research on turnaround strategies typically involves non-outsourcing companies or discusses outsourcing from the perspective of businesses utilizing outsourcing services as a turnaround tactic. This study aims to offer a deeper understanding of the impact of turnaround strategies on outsourcing companies operating within a growing industry.